2021
DOI: 10.5539/elt.v15n1p154
|View full text |Cite
|
Sign up to set email alerts
|

Radio Drama Competition as an Effective Tool to Boost the Motivation and Self-Confidence of Primary and Secondary School English Learners in Hong Kong

Abstract: In this report, we investigate the use of a radio drama competition to boost motivation, self-confidence, and cooperation in language learning for primary and secondary school students in Hong Kong. The results suggest the radio drama competition had a positive impact on increasing motivation, collaboration, and confidence in language learning.  For the study, we used online surveys and interviews with students and teachers who participated in the radio drama competition to examine their percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Another study by Chan & Tang (2022), on the effectiveness of radio drama competition to boost motivation, self-confidence, and cooperation in language learning for primary and secondary school students in Hong Kong. It was found that radio drama competition had a positive impact on increasing motivation, collaboration, and confidence in language learning.…”
Section: Previous Research Concerning Radio Drama In Esl Learningmentioning
confidence: 99%
“…Another study by Chan & Tang (2022), on the effectiveness of radio drama competition to boost motivation, self-confidence, and cooperation in language learning for primary and secondary school students in Hong Kong. It was found that radio drama competition had a positive impact on increasing motivation, collaboration, and confidence in language learning.…”
Section: Previous Research Concerning Radio Drama In Esl Learningmentioning
confidence: 99%
“…In addition, an important factor to mention is that anxiety decreases when students interact orally with their classmates promoting the use of English as a means of communication in class. Anxiety affects second language acquisition and causes poor learners' performance (Chan & Tang, 2022). However, some problems result from oral interaction such as transcribing the responses that are produced by peers in written form to grids created for sharing activities and the difficulty when trying to pronounce some words.…”
mentioning
confidence: 99%